Les processus de contestation dans le cadre des candidatures des villes européennes aux Jeux olympiques et paralympiques 2024 - Bourbillères, H.; Koebel, M (Movement & Sport Sciences - Science & Motricité, 2019)
It is a big challenge for a country or a city to be a candidate for hosting the next Olympic and Paralympic Games (OPG). For a long time, it was a diplomatic decision confined to the secrecy of political and economic circles. Due to some recent events like the rise of the collective protests, new stakeholders as the citizens are included in the bidding process. This research addresses these evolutions by focusing on the citizen involvement during OPG`s bids. This contribution presents the exploratory results of a postdoctoral project (2018-2020). First part presents a literature review about the impacts of major sport events (MSE), arguing the question of the public distrust about the organization of the OPG. Second part analyzes the various cases of applications of European cities to 2024 OPG`s based on a documentary analysis (application form, opinion polls, local press articles). Paris (France) is winner without a referendum, but also without rivals at the end; Rome (Italy) withdrew the bid right after the election of the new mayor due to a new policy line; Hamburg (Germany) organized a referendum and the "no" narrowly won; and Budapest (Hungary) withdrew the bid following economic arguments expressed in students` petition (Momentum).